UJI AKTIVITAS SEDIAAN SALEP DARI EKSTRAK ETANOL KULIT BUAH PISANG BARANGAN (Musa Acuminata colla) TERHADAP BAKTERI PENYEBAB INFEKSI LUKA (Staphylococus aureus) - Samosir, Sri Rezeki; Immanuel, Adhe Christie (JIFI (Jurnal Ilmiah Farmasi Imelda), 2023)
Skin Fruit Banana goods (Musa acuminate Colla) can used as ingredient blocker bacteria. Research this aim for knowing activity antibacterial preparation ointment from extract skin fruit banana goods (Musa acuminate colla) against Staphylococcus aureus. Method Study this conducted Experimental, extract obtained with use method maceration with solvent 96% followed after that the extract was concentrated with rotary evaporator. Ethanol obtained tested Phytochemicals. The results of screenings showed that all of the extracts from skin fruit banana contained flavonoid, alkaloid, steroid, terpenoid and tannin, then made preparation ointment using Vaseline Album base, Adeps Lanae, Paraffin Liquid, Setyl Alcohol and preparation ointment Extract Skin Fruit Banana goods have Concentration 4%, 6%, 8%. Results this show that skin fruit banana goods (Musa acuminate Colla) can formulated as preparation Ointment and Fulfill requirements test quality preparation ointment among them Test Organoleptic, Test Homogeneity, Ph Test, Test Power spread. The results ofthe antibacterial activity test were analyzed using a sumuran method show that formulation preparation ointment extract skin fruit banana goods (Musa acuminate cola ) with concentration 4%, 6%, 8%. Not could hinder growth bacteria and power block. Concluded that the more increase concentration extract, so power a given block the more big to get zone good inhibit _ in growth bacteria (Staphylococcus aureus).